PENERAPAN MODEL PELAYANAN KEPERAWATAN BERBASIS SPIRITUAL DITINJAU DARI ASPEK PROSES ASUHAN KEPERAWATAN SPRITUAL DI RUMAH SAKIT ISLAM FAISAL MAKASSAR - Saharuddin, saharuddin; Safrullah Amir; Rosmina Rosmina (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT MOJOKERTO), 2019)
The spiritual aspect must be considered in the care process because it directly affects the patient's healing quality. This study was developed to study the application of spiritual nursing care model in hospital. This research uses qualitative method through analytical descriptive approach. A total of 9 informants recruited by purposive sampling in this study consisting of head nurse, nurse, and muslim clergy. In-depth interview results in verbatim form tested for reliability and validity using triangulation technique. The results indicate that the process of spiritual nursing care at Faisal Islamic Hospital has adopted 5 stages which include spiritual assessment, spiritual diagnosis, spiritual planning, spiritual implementation, and spiritual evaluation. Nevertheless, the application of the spiritual service model in the hospital has not been optimal.